المرأة ومشاركتها في النشاط الحرفي في المغرب السلامي خلال العهد المرابطي من 448-541ه /1056-1147م - جماعة, علي العجيلي عبد السلام (مجلة الاصالة, 2025)
المرأة ومشاركتها في النشاط الحرفي في المغرب السلامي خلال العهد المرابطي من 448-541ه /1056-1147م